Culture and personality revisited: Behavioral profiles and within‐person stability in interdependent (vs. independent) social orientation and holistic (vs. analytic) cognitive style. Issue 5 (31st December 2019) - Na, Jinkyung; Grossmann, Igor; Varnum, Michael E. W.; Karasawa, Mayumi; Cho, Youngwon; Kitayama, Shinobu; Nisbett, Richard E.
Abstract: Objective: We test the proposition that both social orientation and cognitive style are constructs consisting of loosely related attributes. Thus, measures of each construct should weakly correlate among themselves, forming intraindividually stable profiles across measures over time. Method: Study 1 tested diverse samples of Americans ( N  = 233) and Japanese ( N  = 433) with a wide range of measures of social orientation and cognitive style to explore correlations among these measures in a cross‐cultural context, using demographically heterogeneous samples. Study 2 recruited a new sample of 485 Americans and Canadians and examined their profiles on measures of social orientation and cognitive style twice, one month apart, to assess the stability of individual profiles using these variables. Results: Despite finding typical cross‐cultural differences, Study 1 demonstrated negligible correlations both among measures of social orientation and among measures of cognitive style. Study 2 demonstrated stable intraindividual behavioral profiles across measures capturing idiosyncratic patters of social orientation and cognitive style, despite negligible correlations among the same measures. Conclusion: The results provide support for the behavioral profile approach to conceptualizing social orientation and cognitive style, highlighting the need to assess intraindividual stability of psychological constructs in cross‐cultural research.